2021
DOI: 10.1155/2021/8692328
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporin-4 Autoantibody Detection by ELISA: A Retrospective Characterization of a Commonly Used Assay

Abstract: Objective. Aquaporin-4 (AQP4) serum autoantibodies are detected by a variety of methods. The highest sensitivity is achieved with cell-based assays, but the enzyme-linked immunosorbent assay (ELISA) is still commonly utilized by clinicians worldwide. Methods. We performed a retrospective review to identify all patients at the University of Utah who had AQP4 ELISA testing at ARUP Laboratories from 2010 to 2017. We then reviewed their diagnostic evaluation and final diagnosis based on the ELISA titer result. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…We found that the cell-based biopanning technique was superior to other alternatives using a synthetically generated antibody library. These data agree with other recent reports of cell-based assays offering higher sensitivity and specificity in AQP4 autoantibody detection than AQP4 ELISA assays that use purified antigens [ 41 ]. Moreover, compared to FACS, sorting by cell-based biopanning is quicker, avoids the need for specialized equipment, and better preserves the native conformation of the antigen to facilitate a more effective selection of antigen-binding clones.…”
Section: Discussionsupporting
confidence: 93%
“…We found that the cell-based biopanning technique was superior to other alternatives using a synthetically generated antibody library. These data agree with other recent reports of cell-based assays offering higher sensitivity and specificity in AQP4 autoantibody detection than AQP4 ELISA assays that use purified antigens [ 41 ]. Moreover, compared to FACS, sorting by cell-based biopanning is quicker, avoids the need for specialized equipment, and better preserves the native conformation of the antigen to facilitate a more effective selection of antigen-binding clones.…”
Section: Discussionsupporting
confidence: 93%
“…In the second case, the initial anti-AQP4 antibody test was positive in the CSF (utilizing CBA) but negative in the serum (utilizing ELISA), with positive repeat serological testing (utilizing CBA) 10 months later. Atlhough the initial combination of anti-AQP4 antibody results in this case—CSF positive but serum negative—is highly atypical of NMOSD ( 19 22 ), the initial negative serum test was likely a false negative due to the lesser sensitivity and specificity of the ELISA test compared to the CBA modality ( 23 ). While the cerebrum was spared in Case 3, the thalamus was involved in Case 2, a structure that can be involved in NMOSD ( 24 ).…”
Section: Discussionmentioning
confidence: 88%
“…Five patients in this study tested positive for AQP4‐IgG. Although AQP4‐IgG testing by CBA is highly specific, false‐positive results are recognized to occur with ELISA [35, 36]. Nevertheless, two patients in this study with a final diagnosis of spinal cord neoplasm tested positive for AQP4‐IgG by CBA, one in serum by live CBA and one in CSF with a non‐specified CBA.…”
Section: Discussionmentioning
confidence: 90%